The frequency of cooking dinner at home and its association with nutrient intake adequacy among married young-to-middle-aged Japanese women: the POTATO Study. (2019) - Saito, Aki; Matsumoto, Mai; Hyakutake, Aiko; Saito, Masafumi; Okamoto, Naoko; Tsuji, Masayoshi
Abstract: Home cooking has been suggested as a key to healthy dietary intakes. However, little is known about the association between cooking behaviour and nutrient intake among young-to-middle-aged women. We aimed to investigate the association between home cooking frequency and nutrient intake adequacy among married Japanese women. Self-administered questionnaires were used to assess the weekly frequency of cooking dinner at home and habitual nutrient intake during the preceding month. We evaluated nutrient intake adequacy by comparing the self-reported intake with two indices of the dietary reference intakes for Japanese (2015): the estimated average requirement (EAR) of fourteen nutrients, and the 'tentative dietary goal for preventing lifestyle-related diseases' (DG) of seven nutrients. A total of 143 participants (25–44 years old) completed the questionnaires, with 32·9 % of participants reporting a weekly home cooking frequency of seven times/week. Women with a higher home cooking frequency (seven times/week) were more likely to have children ( P = 0·001) than those with a lower home cooking frequency (0–6 times/week). Of the nutrients evaluated, there was no significant difference between the two groups in meeting EAR and DG. Our findings suggest that daily home cooking may not be necessary to achieve adequate nutrient intake, specifically among married, young-to-middle-aged Japanese women.